2008
DOI: 10.1038/ng.242
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of an AP-2α binding site in an IRF6 enhancer is associated with cleft lip

Abstract: Previously we have shown that nonsyndromic cleft lip with or without cleft palate (NSCL/P)1, is strongly associated with SNPs in Interferon Regulatory Factor 6 (IRF6)2. Here, multispecies sequence comparisons identify a common SNP (rs642961, G>A) in a novel IRF6 enhancer. The A allele is significantly overtransmitted (P=1×10−11) in families with NSCL/P, in particular with cleft lip (CL) but not cleft palate. Further, there is a dosage effect of the A allele, with the relative risk for CL 1.68 for the AG genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
488
7
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(527 citation statements)
references
References 30 publications
23
488
7
9
Order By: Relevance
“…IRF6 gene expression has been shown previously to be regulated by the binding of the p63 transcription factor to an enhancer element located 9.7 kb upstream of the IRF6 transcription start site (55,56). However, IRF6-binding sites in the IRF6 gene have been identified, leading to the suggestion that IRF6 can also mediate its own expression (8).…”
Section: Discussionmentioning
confidence: 97%
“…IRF6 gene expression has been shown previously to be regulated by the binding of the p63 transcription factor to an enhancer element located 9.7 kb upstream of the IRF6 transcription start site (55,56). However, IRF6-binding sites in the IRF6 gene have been identified, leading to the suggestion that IRF6 can also mediate its own expression (8).…”
Section: Discussionmentioning
confidence: 97%
“…31 AP-2a is known to be essential for craniofacial development and cranial closure 32 and has been implemented in NSCL/P. 33 Similarly in the analysis of NSCPO, a suggestive bias for maternal over-transmission was observed for rs6539608 located on chromosome 12q21. No genes or transcripts map to this region, making an interpretation of functional relevance difficult.…”
Section: Discussionmentioning
confidence: 97%
“…7 ). Subsequent analyses identified a causative variant rs642961 in the IRF6 promoter region which disrupts the binding site of the transcription factor AP-2a involved in craniofacial development 8 . In this report, we found that rs642961 was associated with nsCL/P risk in all of the models of inheritance tested, with a 1.6 to almost a threefold increase in risk.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of genetic approaches have been used to identify genes and pathways underlying nsCL/P. Before 2009, only one gene (interferon regulatory factor 6, IRF6) had been identified with a sufficient degree of consistency across studies, thus being considered a true nsCL/P-associated gene [7][8][9] . Association of nsCL/P with single nucleotide polymorphism (SNP) rs642961 in the IRF6 gene located at chromosomal region 1q32 was confirmed in candidate gene and genome-wide association studies (GWAS) of European-derived populations [10][11] .…”
Section: Introductionmentioning
confidence: 99%